Efficacy of single-dose oral secnidazole for the treatment of trichomoniasis in women co-infected with trichomoniasis and bacterial vaginosis: a post hoc subgroup analysis of phase 3 clinical trial data - Christina A Muzny; Olivia T Van Gerwen; Gregory Kaufman; Steven Chavoustie (BMJ Open)
Objectives Bacterial vaginosis (BV) and trichomoniasis are the most common causes of vaginitis. Both infections are associated with increased risk of acquisition and transmission of HIV and other sexually transmitted infections as well as adverse reproductive health outcomes. Co-infection is common, with rates ranging from 60% to 80%. We evaluated the efficacy of single-dose oral secnidazole 2 g for the treatment of trichomoniasis in a subgroup of women co-infected with BV and trichomoniasis.Design Post hoc analysis of data from a phase 3 randomised, double-blind, placebo-controlled, delayed-treatment study.Setting 10 centres in the USA.Participants Subgroup of women (aged ≥12 years) with a confirmed diagnosis of Trichomonas vaginalis and co-infection with BV clinically diagnosed using Amsel’s criteria.Intervention Single dose of secnidazole 2 g or placebo.Outcome measures The primary efficacy outcome was the microbiological cure (negative culture for T. vaginalis) at the test of cure (TOC) visit 6–12 days after dosing in the modified intent-to-treat population (mITT). At TOC, participants received the opposite treatment.Results Of the 131 T. vaginalis-infected participants in the mITT, 79 (60.3%) met ≥3 Amsel’s criteria for BV at enrolment. Microbiological cure rates for trichomoniasis at TOC among this subgroup of women were 97.7% (42/43) for secnidazole and 0% (0/36) for placebo.Conclusion Single-dose oral secnidazole 2 g was highly efficacious in curing trichomoniasis in women co-infected with BV. Appropriate and effective treatment options for co-infection are essential for reducing transmission and reinfection. Secnidazole is the only single-dose medication approved by the Food and Drug Administration for the treatment of BV in women and trichomoniasis in women and men.Trial registration number ClinicalTrials.gov, NCT03935217; post-results.